(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the legal foundations, organizational structure, and role of the “Vatan Tayanchi” (Support of the Motherland) movement, established in Uzbekistan to promote military-patriotic education among children and adolescents, within the framework of state policy. The study analyzes the movement’s objectives, tasks, development fund, and the benefits provided to its members. The research highlights the effectiveness of a comprehensive pedagogical and physical education approach in fostering socially responsible, morally mature, and patriotic youth.